COST - MINIMIZATION ANALYSIS KAPTOPRIL DIBANDINGKAN LISINOPRIL PADA PASIEN HIPERTENSI RAWAT JALAN - Diesty Anita Nugraheni; Tri Murti Andayani (Fakultas Farmasi Universitas Setia Budi, 2015)
Cost minimal of hypertension can saving money because cardiovascular morbidity and mortality. This study intend to know cost minimal among captopril versus lisinopril of outpatients with hypertension, based on hospital aspect. This study was epidemiology survey, with descriptive analysis and retrospective. The subject was outpatients hypertension in RSUP Dr. Sardjito and RS PKU Muhammadiyah Yogyakarta using captopril or lisinopril as new therapy, addition therapy, or replacement therapy, observed in two months therapy. Samples were selected non-randomly with purpose. Number of samples are 50 patients. The cost was direct medical cost of outpatients with hypertension. The analysis of data describe the use of antihypertensive, sum of direct medical cost, and cost-minimization analysis. The results showed that the clinical outcome of captopril and lisinopril was equivalent. The mean direct medical cost in hypentension without compelling indications for captopril was Rp 134.715,41, and lisinopril was Rp 315.093,16. In hypentension with compelling indications diabetes mellitus, mean direct medical cost for captopril was Rp 242.430 and lisinopril was Rp 492.270. Captopril was cost minimal among two diagnosis.